CLL (Community Language Learning) method and Students’ Interest Towards Students’ Speaking Ability - Sugiyani Natalia (Channing : Journal of English Language Education and Literature, 2017)
This study investigate the Influence of CLL Method and Students’ Interest towards the Eleventh Grade of SMA Negeri 1 Buay Madang OKU Timur”. In this research, the writer wants to investigate the students’ speaking ability which is being a necessary subject for the learners in their English communication. The main problem of this study “Is there a significant influence of CLL Method and Students’ Interest towards the eleventh grade students’ speaking ability of SMA Negeri 1 Buay Madang OKU Timur?”. The objectives of this study were to find out whether or not CLL Method and students’ interest influence the students’ speaking ability and there was or no a significant interaction effect of CLL Method and students’ interest toward the Eleventh grade students’ speaking ability of SMA Negeri 1 Buay Madang OKU Timur. This study was purposed at investigating the influence of CLL Method and students’ Interest toward the eleventh Grade students’ speaking ability. The population of this study was 216 students of SMA Negeri 1 Buay Madang OKU Timur. From the population, there were 31 students taken as sample of experimental group and 32 students were as control group. The sample was taken using two stages random sampling. In carrying out the research, the writer used a factorial group design. Finally the calculation using a two-way ANOVA was used to measure an interaction between CLL Method and students interest on their speaking ability. Test of Between-Subjects Effects analyses, the interaction between high and low interest to technique was 0.000, the probability sig. of technique was 0.023, and the significant value of the techniques (CLL and conventional) and the students’ interest were 0.923, and which is higher than the significant level of p-value 0.05, it meant that there was no interaction between students’ interest and techniques. So, the research hypothesis that stated “there is no interaction between CLL Method and interest toward students’ speaking ability” was accepted and the null hypothesis was not rejected based on the data on chapter four.